1992
DOI: 10.1139/g92-127
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomes and DNA of Anguilla anguilla: a study with restriction endonucleases

Abstract: We have studied fixed chromosomes and purified DNA of Anguilla anguilla L. after digestion with HaeIII, AluI, MboI, and DdeI restriction endonucleases. Our data demonstrated (i) confirmation of the heteromorphic nature of NORs, (ii) absence of detectable sex chromosomes, and (iii) presence of discrete intercalary domains in this species. Our data also permitted us to hypothesize the existence of highly repetitive DNAs, localized in specific heterochromatic regions of A. anguilla chromosomes

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
13
0
1

Year Published

1994
1994
2005
2005

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 0 publications
1
13
0
1
Order By: Relevance
“…Great difficulties have arisen in the C-and G-banding studies of amphibians, and only in the last few years data on the sensitivity of chromo somes to the various banding techniques have been reported in teleosteans (Lloyd and Thorgaard, 1988;Cau et al, 1988Cau et al, .1992 Lozano et al, 1991;Sanchez et al, 1991; Hartley, 1991a. b; Padilla et al, I993;Vinaset al, 1994).…”
mentioning
confidence: 99%
“…Great difficulties have arisen in the C-and G-banding studies of amphibians, and only in the last few years data on the sensitivity of chromo somes to the various banding techniques have been reported in teleosteans (Lloyd and Thorgaard, 1988;Cau et al, 1988Cau et al, .1992 Lozano et al, 1991;Sanchez et al, 1991; Hartley, 1991a. b; Padilla et al, I993;Vinaset al, 1994).…”
mentioning
confidence: 99%
“…The sus ceptibility of eel chromosomes to restriction endonuclease treatment changes over time; as the duration of treatment lengthens, the G-bands progressively disappear, leaving a Cband-like pattern (data not shown). Cau et al (1992) ever, their results were not consistent. Cau et al (1992) incu bated their preparations with HaelII for 16 h, whereas we used only 7 h. In this connection.…”
Section: Resultsmentioning
confidence: 83%
“…Cau et al (1992) ever, their results were not consistent. Cau et al (1992) incu bated their preparations with HaelII for 16 h, whereas we used only 7 h. In this connection. Fernandez-Peralta et al (1991) found that the action of Alitl digestion on human chromosomes was also time dependent, the enzyme producing G-band pat terns only with shorter incubation times.…”
Section: Resultsmentioning
confidence: 83%
“…This arm was previously characterized by fluorochrome banding as a GC-rich heterochromatic region (Medrano et al" 1988: Cau et al. 1992.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to its economical value, the eel is of par ticular interest since it represents one of the few fishes with a reasonable and reproducible euchromatic banding pattern (Wiberg, 1983;Sola et al, 1984;Cau et al, 1992). Furthermore, the genome compartmcnializalion values arc close to those ob served in warm-blooded vertebrates (Medrano et al, 1988).…”
mentioning
confidence: 96%